A Novel Sperm-Delivered Toxin Causes Late-Stage Embryo Lethality and Transmission Ratio Distortion in C. elegans - Seidel, Hannah S.; Ailion, Michael; Li, Jialing; van Oudenaarden, Alexander; Rockman, Matthew V.; Kruglyak, Leonid (PLOS Biology, 2011)
A sperm-delivered toxin and an embryo-expressed antidote form a co-adapted gene complex in C. elegans that promotes its own transmission to the detriment of organisms carrying it.